Evaluation of Apparent Diffusion Coefficient Values in Spinal Tuberculosis by Mri - Rajneesh Madhok; Primal Sachdeva (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Spinal tuberculosis presents a radiological challenge in many cases when it presents with atypical pattern of involvement and has to be distinguished from various differentials, which include metastases. In such cases Diffusion Weighted Imaging (DWI) with Apparent Diffusion Co-efficient (ADC) value may play a role in reaching towards a conclusion, thereby preventing unnecessary biopsy in such patients. Aim: Measurement of mean ADC values in tubercular vertebrae and associated collection. Materials and Methods: The study was comprised of 55 patients and was conducted on 3.0 TESLA Siemens machine Magnetom Verio. Patients either known to have tuberculosis or those with classic tuberculous findings were included in the study. All these patients were followed up for post-treatment confirmation and ADC value. All the patients underwent routine MRI along with DW-MRI sequence, ADC values and FNAC/ Biopsy if required. The ADC values were calculated from the involved vertebral bodies and surrounding soft tissue and also from normal vertebrae preferably from one above and below the affected vertebrae to establish ADC of normal vertebrae, which was helpful in treatment response in patients with antitubercular therapy. At least six ADC value was taken from affected vertebrae and soft tissue. Results: The mean ADC value of tubercular vertebrae was found out to be 1.47 ± 0.25 x 10-3 mm2 /sec, of adjacent soft tissue collection (abscess) was 1.94 ± 0.30 x 10-3 mm2 /sec and normal vertebrae was 0.48 ± 0.16 x 10-3 mm2 /sec. ADC value of post treated vertebrae decreased and complete resolution showed ADC near normal vertebrae. Conclusion: Normal range of the ADC values in spinal tuberculosis and associated paravertebral collection may be helpful in the differentiation of spinal tuberculosis from lesions with spinal involvement which are not proven to be tuberculosis and who did not have the classical appearance of either tuberculosis or metastasis. But there exists a zone of overlap of ADC values in metastatic and tubercular vertebrae, which can lead to false negative results. Therefore, in overlap cases there should be correlation with clinical history, other related investigations or biopsy.